Gastrointestinal imaging cases - Levy, Angela D.; Mortele, Koenraad J.; Yeh, Benjamin ([New York] : Oxford University Press, 2013)
Offering 171 unique cases, this book features over 700 high-quality images relating to gastrointestinal cases. The clinically relevant cases cover both benign and malignant conditions and are grouped into 12 sections organized by the parts of the gastrointestinal system.
Series from CIP print record.
Includes bibliographical references and indexes.
Description based on online resource; title from home page (viewed on Aug 12, 2013).
Keywords: Gastrointestinal system -- Diseases -- Imaging -- Case studies